Proposal of a quality management design based on the ISO 17025- 2005 standard in the clinical laboratory of the "Enrique Ponce Luque" Health Center belonging to the health district 12d01 of the city of Babahoyo - Los Ríos - Ecuador - Casco López, María Gabriela; Junco Vaca, Agustín Ignacio; Sterling Varas, Erick Xavier (Ingeniería Química y Desarrollo, 2024)
The authors conducted a clinical laboratory diagnosis through observation, followed functioning of the laboratory on separate days to assess specific aspects included in a checklist based on ISO 17025-2005, plus its own analysis interviews were conducted to all workers to collect data from their perspective and obtain verifiable data, this information was subsequently processed and analyzed in a cause-and-effect diagram ISHIKAWA. Results: 80% of the requirements from the checklist are not meted, partially implemented requirements were 14.29 % and finally 5.71% implemented requirements are met. Conclusions: Overall compliance was low; this allows us to conclude that in terms of calibration and traceability clinical laboratory Enrique Ponce Laquez does not have the minimum requirements for operation in accordance with international standards.